Apakah Beban Kerja, Stres Kerja dan Kualitas Tidur Mempengaruhi Kelelahan Kerja pada Perawat di Rumah Sakit? - Ni Wayan Dimkatni; Oksfriani Jufri Sumampouw; Aaltje Ellen Manampiring (Sam Ratulangi Journal of Public Health, 2020)
Background: Work fatigue is a feeling of fatigue and a decrease in alertness. The word fatigue indicates a different state of the body but all of them result in a decrease in work power and a decrease in the body's resistance to work. Work fatigue factor, contributes 50% or more to work accidents. This study aims to determine the correlation between workload,Â  job stress and sleep quality with work fatigue on nurses in The Regional General Hospital of Bitung City and Budi Mulia Hospital Bitung City. Method: This study used cross sectional design. Respondents in this study were nurses who worked at Intensive Care Unit, Emergency Room and Inpatien Room in The Regional General Hospital of Bitung and Budi Mulia Hospital Bitung North Sulawesi Province. The instrument of this study used questionnaire. Results: The results showed there was correlation between workload (p = 0.000), job stress (p = 0.000) and sleep quality (p = 0.002)Â  with work fatigue. Multivariate analysis showed that the variable most correlated to work fatigue is job stress (Î²=0.370). Conclusion: The conclusion in this study there was a correlation between workload, job stress, sleep quality with work fatigue on nurses in the Hospital. Job stress was the most correlated factor to work fatigue on nurses in the Hospital.